Prognostic value of bioelectrical impedance analysis in head and neck cancer patients undergoing radiotherapy: a VALOR® study - Prior-Sánchez, Inmaculada; Herrera-Martínez, Aura Dulcinea; Zarco-Martín, María Teresa; Fernández-Jiménez, Rocío; Gonzalo-Marín, Montserrat; Muñoz-Garach, Araceli; Vilchez-López, Francisco Javier; Cayón-Blanco, Manuel; Villarrubia-Pozo, Ana; Muñoz-Jiménez, Concepción; Zarco-Rodríguez, Felisa Pilar; Rabat-Restrepo, Juana María; et al. (Frontiers in Nutrition, 2024)
Introduction: Bioelectrical impedance analysis (BIA) serves as a method to estimate body composition. Parameters such as phase angle (PA), standardized phase angle (SPA), body mass cell (BCM), BCM index (BCMI) and fat free mass (FFM) might significantly impact the prognosis of head and neck cancer (HNC) patients. The aim of this study was to investigate whether bioelectrical parameters can be used to predict survival in HNC population and establish the optimal cut-off points for predictive accuracy. Methods: Multicenter observational study was performed across 12 tertiary hospitals in Andalusia (a region from south of Spain). A total of 494 patients diagnosed with HNC between 2020 and 2022 at different stages were included in this study with a minimum follow-up period of 12 months. BIA assessment was carried out during the first two weeks of radical radiotherapy treatment with chemotherapy or other systemic treatments. Multivariate logistic regression of overall survival, complications, hospital admission and palliative care and its relationship with BIA nutritional assessment was calculated. Results: Significant prognostic factors identified in the multivariable analysis encompassed PA, SPA, BCM, and BCMI. Lower PA and BCM values exhibited a significant association with adverse clinical outcomes. A BCM threshold above 17 kg/m 2 was as the most significant predictor for predicting survival within the overall HNC population. PA values <5.1° in men and <4.8° in women displayed the best predictive potential for mortality. Increased PA (as a continuous variable) demonstrated a significantly reduced risk for mortality (OR, 0.64; 95% CI, 0.43-0.94; p<0.05), and a decreased likelihood of hospital admission (OR, 0.75; 95% CI, 0.52-1.07; p<0.05). Higher BCM correlated with a lower risk of mortality (OR, 0.88; 95% CI, 0.80-0.96; p<0.01) and a diminished probability of hospital admission (OR, 0.91; 95% CI, 0.83-0.99; p<0.05). Conclusions: BIA is a crucial tool in the nutritional assessment of HNC patients. BCM and PA are the main bioelectrical parameters to predict clinical outcomes in this population. Future studies are needed to validate BIA variables in large cohort, to ensure whether early intensification of nutritional treatment would improve survival.